Challenges and ongoing initiatives towards better integrated EU scientific advice - Gravanis, Iordanis; Berntgen, Michael; Vamvakas, Spiros; Demolis, Pierre; Foggi, Paolo (Frontiers in Medicine, 2025)
Scientific advice is the main avenue for clarification of EU regulators’ scientific evidence requirements during medicines development. There are multiple avenues for seeking scientific advice in the EU with partially overlapping scope which creates room for divergence and contradictions; simplification and better integration among them could help harmonize EU regulators’ requirements. Interaction with other decision makers providing advice along the lifecycle of medicines and other healthcare solutions reduces development uncertainties. The proposal for a new EU pharmaceutical legislation solidifies existing advice mechanisms and creates new avenues for enhanced integration of development support.